Pengaruh Desain Produk, Harga, dan Citra Merek terhadap Preferensi Konsumen pada Produk Fashion Nafasa Busana Muslimah Kedungwuni - Vina Rizqoeni; Dwi Novaria Misidawati (Journal of Islamic Economics and Finance, 2024)
This study aims to analyze the influence of product design, price, and brand image on consumer preferences for Nafasa Muslimah Fashion Products in Kedungwuni. Consumer preference is one of the key factors that influence purchasing decisions, and can be influenced by various marketing elements, such as design quality, pricing, and brand image strength. The theory used in this study is the Theory of Planned Behavior (TPB), which explains that consumer behavior can be influenced by attitudes, subjective norms, and perceived behavioral control. This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 96 respondents who were consumers of Nafasa Muslimah Fashion products in Kedungwuni, Central Java, with an age range of 20-60 years. Validity, reliability tests, and multiple regression analysis were used to test the relationship between independent variables (product design, price, brand image) and dependent variables (consumer preferences). The results of the study indicate that product design has a significant effect on consumer preferences with a calculated t value greater than the t table (2.771> 1.985) and a significance value of 0.0068 <0.05. Price has a significant effect on consumer preferences with a calculated t value greater than the t table (2.506> 1.985) and a significance value of 0.0139 <0.05. And brand image has a significant effect on consumer preferences with a calculated t value greater than the t table (2.033> 1.985) and a significance of 0.0448 <0.05.